PENGARUH BELANJA KESEHATAN, BELANJA PENDIDIKAN, DAN PERTUMBUHAN EKONOMI TERHADAP IPM DI PROVINSI JAWA BARAT - Sumiyarti, Sumiyarti; Lazuardy Pratama, Charenza (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Efforts to create quality human resources require government intervention. These efforts are carried out in the form of spending or expenditure such as health expenditure and education expenditure. This research aims to analyze the factors that influence the Human Development Index in 27 Regencies/Cities in West Java Province. The dependent variable in this research is the Human Development Index and the independent variables are Health Expenditure, Education Expenditure, and Economic Growth. This research uses a regression method with a panel data model to determine the influence of independent variables, namely Health Expenditure, Education Expenditure, and Economic Growth on the dependent variable Human Development Index (HDI). The data used is secondary data published by the Central Statistics Agency and the Directorate General of Financial Balance (DJPK) of the Ministry of Finance, with an observation period of 2013-2022. The results of the research show that the independent variables, namely Health Expenditure, Education Expenditure, and Economic Growth have a significant and positive effect on the Human Development Index in West Java Province. Significance occurs both in partial testing using the t-test and simultaneous testing using the F-test. The results of this research confirm that serious government spending allocation is very necessary for strengthening human resources.